2018
DOI: 10.1080/13685538.2018.1479385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between microalbuminuria and 25-(OH) vitamin D levels in patients with type 2 diabetes mellitus

Abstract: This study found that the level of microalbuminuria was significantly higher in patients with 25-(OH) vitamin D deficiency compared to patients with 25-(OH) VD insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
3
19
0
1
Order By: Relevance
“…A recent cross-sectional study of 351 Chinese inpatients with T2DM demonstrated that VDD was independently associated with DKD [21]. This was consistent with many previous studies which had linked albuminuria to low vitamin D levels [58][59][60][61][62]. Conversely, several studies reported discordant results [24,63,64].…”
Section: Discussionsupporting
confidence: 83%
“…A recent cross-sectional study of 351 Chinese inpatients with T2DM demonstrated that VDD was independently associated with DKD [21]. This was consistent with many previous studies which had linked albuminuria to low vitamin D levels [58][59][60][61][62]. Conversely, several studies reported discordant results [24,63,64].…”
Section: Discussionsupporting
confidence: 83%
“…DR and DKD are common microvascular complications of diabetes ( 7 ). Many clinical studies have recognized VDD as the risk factor for DR ( 16 , 25 , 41 ) and DKD ( 17 , 42 ), whereas other epidemiological researches showed opposite results ( 21 , 22 , 43 ). In this study, we revealed that the correlation between VDD status and the prevalence of DR or DKD was not statistically significant after adjusting laboratory measurements, diabetic complications, related comorbidities, and medications besides the adjustment for demographics and physical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…T2DM is more common in the elderly patients. In recent years, with the increase in the elderly population, the incidence rate of T2DM has shown an upward trend, and this disease has become a public health problem endangering people's health [9] . The pathogenesis of T2DM has not been fully elucidated and there is still a lack of means to cure T2DM, so the major treatment goal is to control blood glucose [10] .…”
Section: Abstract: Type 2 Diabetes Mellitus Insulin Secretion 25-hydroxyvitamin D3 Correlationmentioning
confidence: 99%